The Role of Motivation and Work Environment to Promote Productivity of Chili Farmers in Magelang - Irhamni, Muhammad Ricza; Muna, Khoirul; Falah, Wildan Yusrul (Indonesian Journal of Agricultural Research, 2024)
This paper examines the impact of motivation and the work environment in supporting the productivity of chili farmers in Magelang. We use managerial work motivation theory to identify farmer motivation and use the work environment as a measuring tool to determine the environmental conditions around agricultural land. The quantitative model is estimated to show that motivation and work environment can significantly boost farmer productivity. The sample in this study was 64 respondents, regression analysis was used in this study using SPSS 22. Farmers with high motivation will increase the productivity of their crops, although this is not significant. Finally, farmers with a good working environment will increase farmer productivity significantly.